Maturidade fisiológica, tolerância à dessecação e longevidade de sementes edulis [(A. St.-Hil., A. Juss. & Cambess.) Hieron. ex Niederl.] - Kaiser, Daiana Karoline (2016)
The identification of physiological maturity allows recognize the moment that the seeds have the highest physiological and associate maturity with the fruit color has practical character, it helps in identifying the appropriate harvest time. Also, identify the response of seeds to desiccation is essential for proper postharvest handling aiming at their conservation. This study aimed to determine whether the physiological maturity of A. edulis seeds is achieved in the same maturation stage, regardless of the collection region and the colorimetry of the fruit can determine the maturity of seeds. In addition, it evaluated the desiccation tolerance and longevity of seeds in ex situ conditions. To determine the maturity of seeds, fruits were harvested in Santa Helena, Entre Rios do Oeste and Guaíra-PR and visually classified into five maturity stages by staining the epicarp and a digital colorimeter. The variables analyzed in the seeds understood morphological characteristics, germination and vigor. In studies of desiccation and longevity, the fruits were harvested in Guaíra-PR. The variables quantified in seeds comprised the determination of water content (WC), dry matter (DM), ratio of seed husk and its (SCR) and the probability of desiccation sensitivity (PSD). Seeds with 30% moisture were dried until they reach 23%, 15%, 10% and 5% moisture. Subsequently, four sub-samples were submitted to germination. At the same time, subsamples with 30% water content, 10% and 5% were stored in permeable packaging to 20.1 °C and 39.1% RH for 180, 270 and 365 days. The stabilization of the dry matter of seeds was found in fruits with orange coloring. With advancing maturity, red fruits possessed seeds with lower moisture, coinciding with the maximum germination percentage and speed, besides generating seedlings with larger size and mass accumulation. The green spectrum discriminated maturity in different places of harvest. Seeds used in the test had desiccation and longevity WC 30.42%, DM 24.99 mg, SCR 0.27 and PSD 7%. The germination, mean germination time, dry mass and length of seedlings remained unchanged after drying to 5% moisture. There accelerating germination of seeds with WC 10% and 5%. The loss of germination was 50% at 116 days (WC 30%) and 232 days (WC 10% and 5%). Seeds stored with WC 5% had lower loss in germination rate and high seedling growth. At the end of storage increased by 15% in the mean germination time, 13% reduction in dry matter 9% and the seedlings length. A. edulis seeds with maturity should be harvested when the fruits are red colored, regardless of harvest or with reflectance values between 28.0 to 49.2 nm in the green range of the color spectrum. A. edulis seed is desiccation tolerant to the removal of 82% of cellular water content (WC 5%), with 50% loss of germination to 232 days